Channel-Length-Dependent Low-Frequency Noise Characteristics of Ferroelectric Junctionless Poly-Si Thin-Film Transistors - Shin, Wonjun; Kim, Sangwoo; Koo, Ryun-Han; Kwon, Dongseok; Kim, Jae-Joon; Kwon, Deok-Hwang; Kwon, Daewoong; Lee, Jong-Ho (Institute of Electrical and Electronics Engineers, 2023)
In this study, we explore the low-frequency noise (LFN) characteristics of hafnium-zirconium ferroelectric junctionless poly-Si thin-film transistors (FE JL TFTs) with different channel lengths (Ls). The findings reveal that the magnitude of 1/f noise decreases with a decrease in L, exhibiting the opposite trend from that of conventional FETs. Additionally, it is observed that the protrusion of poly-Si is more susceptible to damage from tensile stress during post-metal annealing in devices with longer L.